ANALISA PERAN MEDIA DALAM PENCEGAHAN ROKOK PADA KALANGAN REMAJA - Foong, Gabrielle (Jurnal Vicidi, 2025)
This scientific work focuses on the background of education regarding smoking among teenagers in Indonesia. The influence of smoking on teenagers has grown rapidly, affected by both individual and environmental factors. Therefore, the purpose of this work is to create an educational medium for smoking prevention among early teenagers. The research method used is a literature review. The results show that education through media can be an effective tool in increasing teenagers' understanding of the risks of smoking. Hence, an innovative and interactive approach in health promotion is essential to reduce smoking behavior among teenagers.